AMERICAN DREAM IN ARTHUR MILLER’S DEATH OF A SALESMAN - Ellisa Claudia Tamara Setiawan; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2020)
The research is concerned with American Dream in Arthur Miller’s Death of aSalesman. The objectives of the research are to describe Willy Loman’s badattitudes and actions, describe Willy Loman’s good attitudes and actions inachieving American dream, and to analyze the results of the American dreampursuit in the story. The first theory that is used in this research is American valueto figure out Willy Loman’s bad and good attitudes and actions and the secondtheory is American dream that is used to analyze the results of American dreampursuit. While, the method of this research, the writer used descriptive method,and for the technique of data collecting, the writer used document analysis. Then,there are two approaches that are used in the analysis namely sociological andpsychological approaches. In the research, the writer found the bad attitudes andactions in the story of Death of a Salesman through the main character, WillyLoman are maintaining his pride, manipulated by his thought, keeping on hisunreal social status, and pretending to be rich. Moreover, the good attitudes andactions in this story are working hard, initiative and full of ambition, getting ofopportunity, getting ready for the competition, and struggling for his family’s life.Furthermore, the results of the main character in pursuing the American dreamalso found in this story, that are losing the real identity of life, getting jealous ofthe success of the other’s life, living in life of full the illusion and delusional,being a stubborn man, being an arrogant man and the last ending with theunhappy ending life. In conclusion, the main character, Willy Loman could notreach his happiness of his life that is caused by his wrong perspective of his mindabout achieving the American dream. And he decided to end his life by suicidehimself to get the money insurance for his family.